Perlindungan Hukum Terhadap Anak dari Bahaya Penyebaran Radikalisme - Hana Krisnamurti; Nindya Adhisty; Agus Hendrayana; Afrizal Herlambang (LPPM Universitas Langlangbuana, 2026)
Radicalism has become a serious threat to child protection in the digital era. Children are vulnerable groups easily influenced through social media, social environments, and inappropriate parenting patterns. This community service program aimed to increase public understanding regarding legal protection for children from the dangers of radicalism through legal education, digital parenting counseling, and assistance in drafting community-based child protection regulations. The implementation method consisted of three stages: preparation, implementation, and evaluation. The program was conducted in RW 14 Pasanggrahan Village, Ujung Berung District, Bandung City, targeting RT/RW administrators, PKK members, and parents. The results showed an increase in public understanding regarding the dangers of radicalism and the importance of child protection, with achievement levels ranging from 80% to 85%. In addition, an RW regulation regarding curfew implementation for children and adolescents was successfully established as a form of community-based social protection. This program demonstrates that legal education and community participation strengthening are effective approaches in preventing the spread of radicalism among children.